Analisis Strategi Pemasaran Dalam Peningkatan Penjualan Pada Produk Bika Ambon : Studi Kasus Pada Usaha Toko Bika Ambon Nasywa - Maulana Meidiansyah; Tri Auri Yanti; Atika Aini Nasution (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the marketing strategy implemented by Bika Ambon Nasywa, a traditional cake producer located in Sunggal Deli Serdang, Medan City, North Sumatra. A qualitative descriptive approach was used in this study, with data collection techniques through in-depth interviews, observations, and documentation analysis. Data analysis was carried out using the SWOT (Strengths, Weaknesses, Opportunities, Threats) framework to identify internal and external factors that influence the marketing of Bika Ambon Nasywa products. The results of the study indicate that the main strength of the product lies in its distinctive taste and the quality of the raw materials used, while weaknesses include limited product and packaging innovation. Opportunities that can be utilized include increasing consumer interest in traditional culinary and the development of information technology for digital marketing. Threats faced include competition with similar products and changes in consumer preferences. Based on this analysis, it is recommended that Bika Ambon Nasywa increase product innovation, improve packaging design, and utilize digital platforms such as social media for promotion in order to expand market share and increase sales.